2022
DOI: 10.4236/fns.2022.137050
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Palmitoylethanolamide (Levagen+<sup>TM</sup>) Compared to Ibuprofen for Reducing Headache Pain Severity and Duration in Healthy Adults: A Double-Blind, Parallel, Randomized Clinical Trial

Abstract: Background: Palmitoylethanolamide (PEA) has shown promise as an analgesic for those with chronic pain pathologies. With recently increased bioavailability, PEA may also be a treatment for acute pain presentations such as tension-type headaches. Aim: To assess the efficacy of a bioavailable PEA formulation (Levagen+ TM ) for reducing the severity and duration of acute episodes of tension-type headaches when compared to a standard treatment, nonsteroidal anti-inflammatory drug (NSAID) (the comparator). Methods:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…I revert to the body's endogenous analgesic, PEA. With excellent safety data [88,89] and efficacy in numerous models of pain [43,[45][46][47][48][89][90][91], it has recently been found to reduce inflammatory markers and stress in athletes [50] and in Covid patients [92]. Non-addictive and free from withdrawal effects, it attenuates cocaine cravings in pre-clinical models [93] and is currently being trailed for opioid reduction in below knee fracture fixation [94].…”
Section: What Are the Implications For Medical Practice?mentioning
confidence: 99%
“…I revert to the body's endogenous analgesic, PEA. With excellent safety data [88,89] and efficacy in numerous models of pain [43,[45][46][47][48][89][90][91], it has recently been found to reduce inflammatory markers and stress in athletes [50] and in Covid patients [92]. Non-addictive and free from withdrawal effects, it attenuates cocaine cravings in pre-clinical models [93] and is currently being trailed for opioid reduction in below knee fracture fixation [94].…”
Section: What Are the Implications For Medical Practice?mentioning
confidence: 99%
“…Unlike OTC medications such as ibuprofen and acetaminophen which inhibit the COX pathway, PEA's pleiotropic effects are likely due to its ability to affect multiple pathways at different receptor sites e.g., proliferator-activated receptor alpha (PPARα) and G protein-coupled receptor 55 (GPR55) receptors and indirectly on cannabinoid receptor type 1 and 2 (CB 1 and CB 2 ); amongst others [21]. Multiple intervention studies have found that PEA doses of between 300 and 1200 mg are effective in the management of pain associated with osteoarthritis and similar dosing relieves headache pain to a similar degree as ibuprofen [22][23][24][25]. Additionally, PEA has shown to improve sleep quality and duration, which may be of benefit to athletes as sleep deprivation has shown to negatively impact skeletal muscle hypertrophy and strength performance [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…PEA is often used to treat both acute and chronic disease stages and has been recognised for its ability to regulate numerous systems involved in inflammation, pruritus, and pain with no documented side effects [17,18]. In eczemalesioned skin, PEA is naturally recruited in high levels, and this is hypothesised to be a direct response to enable the down regulation of mast cell activity and function [19,20].…”
Section: Introductionmentioning
confidence: 99%